Feasibility and effectiveness of second-line chemotherapy with mitomycin C in patients with advanced penile cancer - Draeger, Desiree Louise; Hakenberg, Oliver W. (Frontiers in Urology, 2024)
Background: Triple-drug cisplatin-and taxane-based chemotherapy is the standard treatment for metastatic penile squamous cell cancer (PeSCC) with a moderate response rate of 30% to 38%.Relapse after first line chemotherapy has a poor prognosis and there is no established second line treatment. Mitomycin C (MMC) is used as an effective chemotherapy in squamous cell carcinoma of other localities. We therefore used MMC as a single agent for second line treatment in advanced PeSCC.Methods: Nine patients (median age 63 years (31-81 years)) after inguinal and pelvic lymphadenectomy and progression after first line chemotherapy received second-line treatment with 20 mg MMC intravenously weekly. The median number of cycles of MMC was 6 (2-12) and the median cumulative dose was 120 mg absolute (40-240 mg). Toxicity and treatment responses were evaluated, the latter by 18-FDG-PET/CT.Results: CTCAE grade 3-4 thrombocytopenia and grade 2-3 leukopenia occurred in all patients, as did anemia. In seven patients, the application interval had to be extended due to thrombocytopenia. Stable disease was achieved in two patients, all others progressed under treatment. Seven patients died of disease, mostly 6 months after starting MMC therapy. Of the two patients who responded with disease stabilization, one died of progressive disease 14 months after MMC treatment. The other responding patient has been stable for over one year and is still on treatment and tolerates the treatment well with good quality of life.Conclusion: MMC has only moderate efficacy as a second line treatment in patients with metastatic PeSCC. Hematological toxicity is marked.